A public sector case study on evaluating and managing the benefits of IS/IT - Lin, Chad; Pervan, Graham; McDermid, Donald (The Japan Society for Management Information (JASMIN), 2002)
The issue of expected and actual benefits realised from IS/IT investments has generated a significant amount of debate in the IS/IT literature amongst the researchers, academics, and practitioners. As part of a research program one survey and two in-depth case studies of these practices and processes in large Australian organisations were conducted. A number of issues and problems have emerged from the analysis of the data collected and an IS/IT investment evaluation and benefits realisation framework was developed.